Isotopic insights into mesopelagic niche space and energy pathways on the southern Kerguelen Plateau. (April 2020) - Woods, Briannyn; Walters, Andrea; Hindell, Mark; Trebilco, Rowan
Abstract: Mesopelagic fish are an important but poorly understood mid-trophic component of pelagic food webs. There are major uncertainties regarding their trophodynamics and their overall contribution to the broader Southern Ocean food web. This study aimed to investigate the trophic role of mesopelagic fish in the region of the southern Kerguelen Plateau, an area of known importance to an abundant and diverse community of marine predators. We used carbon and nitrogen stable isotopes to quantify the isotopic niches of key mesopelagic fish species (six from the family Myctophidae, and one from Bathylagidae), and assessed variation along the δ 15 N (resource use) and δ 13 C (carbon source) axes between species. The assemblage of key mesopelagic fish occupied similar isotopic niche space with overlap among species in both δ 13 C and δ 15 N values. Baseline corrected δ 15 N values provided evidence of latitudinal trends in trophic position (TP). Trophic position estimates of taxa in the southern region of our study area spanned slightly less than 1 TP (mean TP 2.9–3.7); and 1 TP in the northern region (mean TP 3.2–4.2). We found evidence of trophic partitioning between species with differences in niche utilization (resource or habitat use). Factors reducing trophic competition include the relative importance of Euphausia superba as a prey item, vertical distribution of consumer and prey, and migratory behaviours. Size-based trophic structuring between species was evident with larger species displaying higher average δ 15 N values compared to smaller species. However, fish standard length explained little of the variation in δ 15 N values at the species level, suggesting within species changes in trophic position with body size is not a predominant driver of trophic structure in our study region. Overall, our analysis demonstrated the structural complexity and spatial variation of the food web in the region of the southern Kerguelen Plateau.